Efficient nickel and copper-based catalysts supported on modified graphite materials for the hydrogen production from formic acid decomposition - Faroldi, Betina María Cecilia (2022)
Ni, Cu and Ni-Cu catalysts supported on high surface area graphite were synthesized by incipient wet impregnation. Also, the effect of doping the graphite support with alkali oxides (Li, Na and K) was studied. The catalysts were tested in the formic acid decomposition reaction to produce hydrogen. The bimetallic Ni-Cu catalyst doped with K showed the best catalytic performance with 100% conversion of formic acid at 130 °C and a 95% of selectivity to hydrogen. The turnover frequency (TOF) of the catalysts follows the order: Ni-Cu/K > NiCu/Na > Ni-Cu > Ni-Cu/Li. While the order for the apparent activation energy values is: Ni-Cu > Ni-Cu/Li > Ni-Cu/Na > Ni-Cu/K. The mechanism of the reaction is approached by programmed temperature surface reaction (TPSR) experiments and attenuated total reflectance (ATR). The greater catalytic activity of the Ni-Cu catalyst doped with potassium is ascribed to the lower stability of the formate, bicarbonate and carbonate species on its surface.